Effect of Using Different Levels of Commercial Micronutrients Complex and Humic Acid on Some Growth and Yield Attributes of Barley Crop Hordeum Vulgare L - Mohammed, Saja Abdullah; Aljasimee, Kawther Hashim Abar; Mazene, Lamyaa Hussein Mousa (American Journal of Biodiversity, 2026)
A field experiment was carried out of the winter agricultural season 2024-2025 of the winter agricultural season in Shafi'iyya city to know the effect of using a commercial micronutrient mixture and humic acid and their interaction on some growth characteristics and yield of the local barley crop. The experiment was conducted according to factorial experiments with two factors and three replicates. The first factor was spraying with a commercial micronutrient mixture (M0: without spraying, M1: 50 ml/L-1, M2: 100 ml/L-1). The second factor was spraying with humic acid (H0: without spraying, H1: 100 ml/L-1, H2: 150 ml/L-1). The results of the statistical analysis showed that spraying of a commercial micronutrient mixture and humic acid, each separately, recorded significant differences on all studied characteristics such as plant height, spike length, leaf area, number of spikes per plant, weight of 1000 grains, grain yield, and yield. Straw and biological yield As for the interaction between the commercial micronutrient mixture and humic acid, the M2H2 treatment was one of the best experimental treatments, as it exceeded on them significantly and recorded the highest values for all the mentioned traits. Hence, we conclude that the use of the commercial micronutrient mixture and humic acid had a clear effect on the growth performance and yield of local barley.